Facultative Teaching of Crafts in Lithuania in 1958-1990 - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 1996)
Facultative teaching may have different forms, its content is determined by the teacher. This kind of teaching of crafts was introduced in Lithuania in 1958. The article presents a history of development of facultative teaching in sixth, seventh and eighth decades. At the present moment time for the facultative teaching is used on a voluntary basis: it depends on traditions of the school, interests of pupils and qualifications of teachers. The article concludes that now there is a small number of pupils attending facultative lessons. One of the main problems is weak material base of most of the schools. Pupils attendance of facultative lessons should remain voluntary.